The Effect of Credit among Micro, Small, and Medium Enterprises on Income Inequality in Indonesia - Desfiandi, Alvin; Putra, Rama Prima (Universitas Prasetiya Mulya, 2023)
Income inequality has become a growing global concern during the last two decades. High income inequality can hinder economic growth, and in the case of Indonesia, the Gini coefficient continues to show an increasing trend. One of the factors that increase the level of income inequality is inequality in business opportunities and access to capital. To address this issue, the government created a credit program to benefit micro, small, and medium enterprises (MSMEs). MSME loans are basically designed to increase equality through the promotion of business opportunities. The authors seek to study the impact of MSME credit on income inequality in Indonesia using panel data with random effects in 33 provinces from 2005-2016. The results of this study are expected to provide an overview of whether the existing MSME credit program has been running effectively or not.